Study Protocol: Randomised controlled trial to investigate the functional significance of marginal riboflavin status in young women in the UK (RIBOFEM) - Williams Elizabeth A (BMC Public Health, 2009)
Abstract Background The functional significance of moderate riboflavin deficiency as it is currently assessed is not well understood. Animal and human studies have suggested a role for riboflavin in the absorption and mobilisation of iron and as such may be important in maintaining haematological status. Recent National Diet and Nutrition Surveys in the United Kingdom have shown that young women in particular are at risk of moderate riboflavin deficiency and low iron status. Methods/Design A randomised placebo controlled intervention trial was conducted to investigate the effect of riboflavin supplementation on various measures of haematological status in a group of moderately riboflavin deficient young women aged 19 to 25 years. Women who were low milk consumers were initially screened for riboflavin status as assessed by the erythrocyte glutathione reductase activation coefficient assay (EGRAC). One hundred and twenty three women with EGRAC values >1.40 were randomised to receive 2 mg, 4 mg riboflavin or placebo for 8 weeks. In addition 36 of these women were randomly allocated to an iron bioavailability study to investigate the effect of the intervention on the absorption or utilisation of iron using an established red cell incorporation technique. Discussion One hundred and nineteen women completed the intervention study, of whom 36 completed the bioavailability arm. Compliance was 96 ± 6% (mean ± SD). The most effective recruitment strategy for this gender and age group was e-communication (e-mail and website). The results of this study will clarify the functional significance of the current biochemical deficiency threshold for riboflavin status and will inform a re-evaluation of this biochemical threshold. Trial Registration Current Controlled Trials Registration No. ISRCTN35811298